Thermographic appearance of the surface during the process of wound healing - Srigiriraju, Vedavyas; Ramamohan, P; Katikala, Muniraju; Reddy, Vishnu Vardhan; Agrawal, Amit (Indian Journal of Case Reports, 2019)
-